بنيية الشخصية في قصة مهدي والقلادة السحرية ل : ليندة عيادي -مقاربة سيميائية - مرغني, أميرة عائشة (University of El-oued, 2022)
الملخص: يتناول هذا البحث جانبا من جوانب البناء السردي في القصة وهو الشخصية، حيث تعتبر هذه الأخيرة العمود الفقري الذي تقوم عليه كل القصص، ولهذا كانت دراستنا المعنونة بالبنية الشخصية في قصة مهدي والقلادة السحرية، حيث تبين لنا هذه القصة انتصار الخير على الشر . وحاولنا من خلال هذه القصة الكشف على الجوانب الداخلية والخارجية والاجتماعية والفكرية للشخصيات المتواجدة في القصة، معتمدين عن المنهج السيميائي لأنه منهج تحليل يتيح للباحث الحرية في التحليل . This research deals with an aspect of the narrative structure in the story, which is the character, as the latter is the backbone on which all stories are based. That is why our study was entitled the personal structure in the story of Mahdi and the magic necklace, where this story shows us the victory of good over evil. Through this story, we tried to reveal the internal, external, social and intellectual aspects of the characters present in the story, relying on the semiotic method because it is an analysis method that allows the researcher the freedom to analyze.
Keywords: بنية الشخصية - قصة مهدي والقلادة السحرية - ليندة عيادي; Character Structure - The Story of Mehdi and the Magical Necklace - Linda Ayadi